2022
DOI: 10.3390/healthcare10081406
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nurses’ Working Experiences during the First Wave of COVID-19 Outbreak

Abstract: During the COVID-19 outbreak, nurses employed in the clinical sector faced a number of difficulties associated with excessive workload, increased stress, and role ambiguity, which impacted nurses themselves and patient care. The aim of the present study was to investigate how Greek hospital nurses working in non-COVID units experienced the virus outbreak during the first wave of the pandemic. A descriptive qualitative research design was applied using a content analysis approach. To recruit the study participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(130 reference statements)
1
1
0
Order By: Relevance
“…The primary finding from this study was that nurses were witnessing and experiencing unprecedented suffering that became unbearable while working during the COVID-19 pandemic. This finding is supported by current literature on nurses' experiences working globally during the COVID-19 pandemic (Catania et al, 2021; Galanis et al, 2022 ; Halcomb et al, 2020 ; Stravropoulou et al, 2022 ). Nurses in this study described not just physical human suffering but also bore witness to patients and their loved ones' psychological suffering related to mandated isolation.…”
Section: Discussionsupporting
confidence: 80%
“…The primary finding from this study was that nurses were witnessing and experiencing unprecedented suffering that became unbearable while working during the COVID-19 pandemic. This finding is supported by current literature on nurses' experiences working globally during the COVID-19 pandemic (Catania et al, 2021; Galanis et al, 2022 ; Halcomb et al, 2020 ; Stravropoulou et al, 2022 ). Nurses in this study described not just physical human suffering but also bore witness to patients and their loved ones' psychological suffering related to mandated isolation.…”
Section: Discussionsupporting
confidence: 80%
“…In consistency with the findings of the present study, Feder et al's study highlights the importance of sharing feelings of loss and mourning in cases where relatives were unable to be next to their loved ones even after death [ 34 ]. Despite the physical and emotional burden that this issue involved, nurses demonstrated high levels of empathy, professional responsibility, and dedication by standing next to the patients and their families in difficult moments [ 12 , 35 , 36 ]. To a further extent, the patients’ families appeared to have a substantial role in the nurses' well-being and satisfaction, especially when caring for terminally ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases where face-to-face contact between family and patient was exceptionally scheduled, nurses felt relieved and emotionally discharged [ 11 ]. During the pandemic, nurses were identified as the professionals with the greatest physical and emotional burden and yet as those who remained committed to providing high-quality care to their patients [ 2 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, the overall score was significantly different at the study level in only one study [ 24 ], where several items, all in the same direction, indicated a higher UNC occurrence among COVID-19 patients. The study was performed in the first wave when nurses were unprepared, exposed to unprecedented organisational changes, emotionally burdened, fearful, and in high levels of uncertainty [ 42 ]. Conversely, no differences, except for one item indicating less UNC among COVID-19 patients, were found by Cengia et al [ 26 ] in their study conducted in the second wave.…”
Section: Discussionmentioning
confidence: 99%